2007 41st Annual Conference on Information Sciences and Systems 2007
DOI: 10.1109/ciss.2007.4298333
|View full text |Cite
|
Sign up to set email alerts
|

Communication-Based Motion Planning

Abstract: The conventional philosophy in designing mobile networks is that network node movement should be independent of network state. However, there are practical situations where movement decisions may be modified to ensure connectivity. For example, emergency responders in a crisis region relying upon an ad hoc network may need constant reliable communications and therefore adjust their search plan to stay connected, though aspects of their mission may override their objective of staying connected. We present a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It is shown that while certain reconfigurations are possible using the presented algorithm, other require global decision making. While Spanos and Murray view maintaining connectivity as a constraint, others see it as a utility that can be optimized in the case of sparse connectivity (Fridman et al, 2007). When a group of agents must move between two positions and the current motion plan does not take communication constraints into consideration, small changes can be made to the trajectory, thereby improving the connectivity of the network.…”
Section: Related Workmentioning
confidence: 99%
“…It is shown that while certain reconfigurations are possible using the presented algorithm, other require global decision making. While Spanos and Murray view maintaining connectivity as a constraint, others see it as a utility that can be optimized in the case of sparse connectivity (Fridman et al, 2007). When a group of agents must move between two positions and the current motion plan does not take communication constraints into consideration, small changes can be made to the trajectory, thereby improving the connectivity of the network.…”
Section: Related Workmentioning
confidence: 99%
“…where the objective function Our interest in this problem is motivated by the communications relay problems common, for instance, in robotics [2][3][4]16,17,19,21,27,[30][31][32]34], where it is required to survey some target located in t and convey the gathered information back to a base station located in s. One or more unmanned aerial or ground vehicles (UAVs or UGVs) are used as relays. The set X is defined by the terrain within the area of interest.…”
Section: Introductionmentioning
confidence: 99%